The effect of supplementing maize stover with cowpea (Vigna unguiculata) haulms on the intake and growth performance of Ethiopian sheep - Koralagama, K.D.N.; Mould, F.L.; Fernández Rivera, S.; Hanson, Jean (Elsevier, 2008)
This study compared the effect of supplementing maize stover (MS) with cowpea (Vigna unguiculata) haulms or commercial concentrate (CC) on feed intake, nutrient digestibility, live weight gain and carcass yield of male Ethiopian Highland sheep. Two cowpea genotypes, 12688 (forage) and IT96D-774 (dual-purpose), were used. A randomised block design was applied with groups of eight sheep, blocked by weight, allocated to one of six treatments; MS ad libitum either unsupplemented or supplemented daily with 150 or 300 g dry matter (DM) of either cowpea or CC. MS contained more neutral detergent fibre (NDF), acid detergent fibre (ADF) and lignin than either cowpeas or CC. Crude protein (CP) content of the forage-type cowpeas was higher than either dual-purpose or CC, while MS had the lowest CP content. Relative to the negative control group, cowpea at either level significantly (P < 0.01) increased both MS intake and total NDF and lignin. Supplementation significantly (P < 0.01) increased nitrogen (N) intakes relative to the negative control, with N intake for CC and dual-purpose cowpea (high level) being similar to the intakes for cowpeas at 150 g. N intake with the forage-type cowpea offered at higher levels was significantly (P < 0.01) greater than the other groups. No significant differences (P > 0.01) in MS intake were identified between cowpeas at either level or CC and, although intake level of CC increased, it did not differ significantly from the negative control group. Supplementation significantly (P < 0.01) improved average daily gain, with the negative control group losing weight over the experimental period, and increased final live weight, carcass cold weight and dressing percentage. Supplementation significantly improved the apparent digestibility of DM, organic matter and NDF, with no significant difference found between cowpeas at either level. N retention was negative for sheep offered only MS, but positive with all supplements, with cowpeas improving N retention to a greater extent than CC. Interestingly, N retention/N intake was higher with cowpeas offered at the lower level suggesting an improvement in utilisation efficiency. The results indicate that the supplementation of MS with cowpea enhanced ruminant production through improvements in digestibility and intake. Further, as production improvements associated with the two levels of supplementation did not differ significantly, it is suggested that where limited quantities of cowpea are available, it may be of greater nutritional benefit to offer smaller quantities over an increased number of animal days.